Tumor Ablation 2012
DOI: 10.1007/978-94-007-4694-7_6
|View full text |Cite
|
Sign up to set email alerts
|

In situ Tumor Ablation with Radiation Therapy: Its Effect on the Tumor Microenvironment and Anti-tumor Immunity

Abstract: The delivery of external beam radiation therapy (RT) for cancer with intent to cure has been optimized over the last 80 years and standardized to a protocol with doses fractionated into around 2 Gy amounts delivered daily five times per week to the tumor with a relatively homogeneous field and with the total dose being determined by what adjacent late responding normal tissues might tolerate. The radiobiological principles that underlie the success of such treatments have been elaborated with the most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…It has been suggested that the high efficacy of SBRT and SRS is due to their ability to stimulate antitumor immunity (3335). However, it is unlikely that the massive secondary cell death which occurs within 2 to 3 days after an exposure to high-dose irradiation is caused by elevation of antitumor immune response, because a significant increase in tumor-specific immune systems as a result of high-dose irradiation of tumors takes longer than at least 1 week (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the high efficacy of SBRT and SRS is due to their ability to stimulate antitumor immunity (3335). However, it is unlikely that the massive secondary cell death which occurs within 2 to 3 days after an exposure to high-dose irradiation is caused by elevation of antitumor immune response, because a significant increase in tumor-specific immune systems as a result of high-dose irradiation of tumors takes longer than at least 1 week (34).…”
Section: Discussionmentioning
confidence: 99%
“…Several modes of EBRT were developed such as stereotactic radiotherapy (SRT), stereotactic body radiation therapy (SBRT), its extension stereotactic ablative radiotherapy (SABR), and lately, intensity modulated radiation therapy (IMRT) (29).…”
Section: Radiationmentioning
confidence: 99%
“…It has been reported that high dose hypo-fractionated irradiation promotes anti-tumor immunity [ 37 38 39 40 ], whereas multi-fractionated radiotherapy with a small dose per fraction suppresses immune competency of the host. Finkelstein et al [ 37 ] attributed the increase in anti-tumor responses by SBRT to elevation of the expression of immune-modulator molecules such as histocompatibility complex, adhesion molecules, heat shock proteins, inflammation mediators, immunomodulating cytokines, and death receptors on the surface of tumor cells.…”
Section: Indirect Tumor Cell Death Due To Immune Response In Sbrt Andmentioning
confidence: 99%